KEPASTIAN HUKUM PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KELURAHAN CIMPAEUN - Salsa Maulida (2022)
At this time the Minister of Agrarian Affairs is trying to deal with the land problem. The problem of land upstream, because there are still many plots of land that have not been registered. Thus, the Ministry of Agrarian affairs and Spatial Planning has a serious commitment to eradicate the practice of the land mafia in Indonesia, one of which is the implementation of the Complete Systematic Land Registration (PTSL) program. Depok City is one of the areas for the implementation of the PTSL program, so Cimpaeun Village is one of the villages targeted by PTSL. So it is necessary to know whether the PTSL in Cimpaeun Village has provided legal certainty and whether the principles for the implementation of PTSL in Cimpaeun Village have been fulfilled. The purpose of this study is to explain legal certainty through PTSL and to analyze the principles in the implementation of PTSL in Cimpaeun Village. The method used in this study is Empirical Legal Research, where this research is carried out by looking at the legal reality in society. This research shows that the implementation of PTSL in Cimpaeun Village still does not apply the principle of fast and smooth and safe land registration properly, because there are several problems, such as there are overlapping problems and in terms of filings that sometimes cannot be completed by the applicant, which causes the implementation of PTSL in Cimpaeun Village to be hampered, so that some communities in Cimpaeun Village have not received legal certainty. Keywords: Complete Systematic Land Registration, Legal Certainty, Quick Principle, Current Principle, Safe Principle